Alterations in the Levels of ACh and Associated AChE in the Tissues of Fresh Water Fish Cirrhinus mrigala Exposed to Deltamethrin - M David, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Alterations in the Levels of ACh and Associated AChE in the Tissues of Fresh Water Fish Cirrhinus mrigala Exposed to Deltamethrin